STUDI PENURUNAN KANDUNGAN TOTAL COLIFORM DENGAN MENGGUNAKAN KOMBINASI VERTICAL FLOW ROUGHING FILTER (VRF) DAN HORIZONTAL FLOW ROUGHING FILTER (HRF) PADA AIR BUANGAN DOMESTIK ARTIFISIAL - Irma Suryanti; Ganjar Samudro; Sri Sumiyati (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTThis research is aims to reduce the content of total coliform bacteria in domestic wastewater using a combination of vertical flow roughing filter (VRF) and horizontal flow roughing filter (HRF) for each variation of flow rate, the type and the size of filter media. Domestic wastewater influent is used as an artificial wastewater containing total coliform bacteria sample 2400 MPN/100 ml. The results of the best drop reaches 0 MPN/100 ml sample contained in VRF combination with medium-sized fine charcoal filter (10 mm,6mm and 3mm) on the flow rate 0.0926 liters/hour.Variations in discharge and the size of filter media for total coliform bacteria indicates a decrease inversely proportional relationship, where the smaller size of the discharge and the filter media decreased total coliform bacteria. As for the type of filter media, charcoal filter media types work better than gravel to reduce the content of total coliform bacteria.